Curable resin composition, pattern, and image display device
By using alkali-soluble resin and multifunctional epoxy oligomer in the curable resin composition, the softening point and post-drying temperature are adjusted, and the problem of insufficient pattern durability and chemical reagent resistance in the low-temperature process is solved, and the problem of inadequate pattern durability and chemical reagent resistance in the low-temperature process is achieved. Efficient pattern formation and adhesion improvement on flexible polymer materials.
Patent Information
- Application Number
- CN202110193302.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-02-04
- Filing Date
- 2021-02-20
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2041-02-20
AI Technical Summary
In the prior art, it is difficult to form a pattern with durability and chemical reagent resistance in a low temperature process, especially on a flexible polymer material substrate, where the reactivity of the thermosetting resin decreases and the durability of the pattern decreases.
A curable resin composition containing an alkali-soluble resin and a multifunctional epoxy oligomer is used to optimize the thermal curing reaction by adjusting its softening point and post-baking temperature, thereby improving the chemical reagent resistance and adhesion of the pattern.
Under a low temperature process below 100°C, patterns with excellent chemical reagent resistance, adhesion and curing density can be produced to avoid surface damage or swelling, and are suitable for use in organic light emitting display devices.
Smart Images

Figure CN113281965B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a curable resin composition capable of forming a pattern having excellent chemical resistance, a pattern formed from the curable resin composition, and an image display device including the pattern. Background Art
[0002] In the field of displays, curable resin compositions are used to form a variety of cured patterns such as photoresists, insulating films, protective films, black matrices, columnar spacers, etc. Specifically, the curable resin composition is selectively exposed and developed by a photolithography process to form a desired pattern. In this process, in order to improve the yield in the process and improve the physical properties of the application object, a curable resin composition with high sensitivity is required. Curable resin compositions can be divided into thermosetting and photocurable (photosensitive) according to the curing mechanism.
[0003] The pattern formation of the photocurable resin composition relies on the change in polarity and crosslinking reaction of the polymer caused by photolithography, that is, photoreaction, and in particular, the change in solubility in solvents such as alkaline aqueous solutions after exposure is utilized.
[0004] Pattern formation using a photocurable resin composition is divided into positive and negative types according to the solubility of the exposed part in the developer. In a positive photoresist, the exposed part is dissolved by the developer, while in a negative photoresist, the exposed part is insoluble in the developer and the non-exposed part is dissolved to form a pattern. The binder resins, crosslinking agents, etc. used in positive and negative types are different from each other.
[0005] In recent years, the use of touch screens with touch panels has exploded, and flexible touch screens have recently received great attention. Therefore, the materials of various substrates used in touch screens should have flexible properties, and the materials that can be used are also limited to flexible polymer materials, and the manufacturing process is also required to be carried out under milder conditions. Therefore, the need to change the curing conditions of thermosetting resin compositions from the previous high-temperature curing to low-temperature curing has also become prominent, but low-temperature curing has problems such as reduced reactivity, reduced durability of the formed pattern, and reduced chemical resistance.
[0006] Korean Patent Registration No. 10-1682006 discloses a photosensitive resin composition comprising a polyimide resin of a specific structure, a photocurable multifunctional acrylic compound, an epoxy resin, and a photoinitiator, but has a limitation in that the required durability cannot be exhibited under low-temperature curing conditions of 100° C. or less.
[0007] Prior art literature
[0008] Patent Literature
[0009] Korean registered patent No. 10-1682006 Summary of the invention
[0010] Issues to be solved
[0011] The object of the present invention is to provide a curable resin composition, in which, for a pattern formed after photocuring, a thermal curing reaction is easily carried out due to an alkali-soluble resin and a multifunctional epoxy oligomer having a suitable softening point at the temperature of the thermal curing process, thereby being able to produce a pattern with improved chemical resistance.
[0012] Solution to the problem
[0013] In order to achieve the above object, the present invention provides a curable resin composition, characterized in that it comprises an alkali-soluble resin (A), a multifunctional epoxy oligomer (B), a photopolymerizable unsaturated monomer (C), a photopolymerization initiator (D) and a solvent (E), and when the post-bake temperature is T PoB , and the softening point of the alkali-soluble resin (A) or the multifunctional epoxy oligomer (B) is T Soft When (T PoB +T Soft ) / T PoB The value of T SP The alkali-soluble resin (A) comprises a SP The photocurable alkali-soluble resin (A-1) and T SP The value of T of the thermosetting alkali-soluble resin (A-2) is 1.2 to 2.1, and the T of the polyfunctional epoxy oligomer (B) is SP The value is 1.3~2.2.
[0014] Furthermore, the present invention provides a pattern formed from the curable resin composition and an image display device including the pattern.
[0015] Effects of the Invention
[0016] The present invention can provide the following curable resin composition: for the pattern formed after photocuring, the thermal curing reaction is easy to proceed due to the alkali-soluble resin and multifunctional epoxy oligomer having a suitable softening point at the temperature of the thermal curing process, thereby being able to produce a pattern with improved chemical resistance, adhesion and curing density without causing surface damage, swelling or film shrinkage.
[0017] Even when the curable resin composition of the present invention is used to manufacture a pattern through a low-temperature process below 100°C, the resin composition has a softening point suitable for the thermal curing temperature and has excellent physical properties such as adhesion to the underlying substrate and resistance to chemical reagents. It is particularly suitable for manufacturing patterns for organic light-emitting display devices that require a low-temperature process temperature below 100°C.
[0018] Specifically, the photocurable thermosetting resin composition of the present invention has a softening point lower than the thermal curing process due to the alkali-soluble resin and the multifunctional epoxy oligomer having an epoxy equivalent of 250 g / eq. or less, and is easy to thermally cure due to the abundant epoxy groups, so that a pattern having excellent curing density and excellent chemical resistance can be manufactured. Therefore, a pattern for an organic light-emitting display device can be manufactured that has excellent adhesion even after being treated with an etchant and a stripper, and does not cause surface damage, swelling, or film shrinkage. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The graph shows the change in film shrinkage and adhesion of the curable resin compositions (alkali-soluble resin and multifunctional epoxy oligomer) of the embodiments of the present invention and the comparative examples and T SP A graph showing the correlation of the values of 80 total.
[0020] Figure 2 It is for the above Figure 1 A zoomed-in graph of a critical point in the graph.
[0021] Figure 3 The graph shows the film shrinkage change and adhesion of the curable resin compositions (alkali-soluble resin and multifunctional epoxy oligomer) of the examples and comparative examples of the present invention and T SP A graph showing the correlation of the total values of 100.
[0022] Figure 4 It is for the above Figure 3 A zoomed-in graph of a critical point in the graph.
[0023] Figure 5 The graph shows the film shrinkage change and adhesion of the curable resin compositions (alkali-soluble resin and multifunctional epoxy oligomer) of the examples and comparative examples of the present invention and T SP 230 is a graph showing the correlation of the total values.
[0024] Figure 6 It is for the above Figure 5 A zoomed-in graph of a critical point in the graph. DETAILED DESCRIPTION
[0025] The present invention provides a curable resin composition, a pattern formed by the curable resin composition, and an image display device comprising the pattern. The curable resin composition comprises an alkali-soluble resin (A), a multifunctional epoxy oligomer (B), a photopolymerizable unsaturated monomer (C), a photopolymerization initiator (D), and a solvent (E). The alkali-soluble resin (A) comprises one or more selected from a photocurable alkali-soluble resin (A-1) and a thermosetting alkali-soluble resin (A-2).
[0026] In the above alkali-soluble resin (A), the photocurable alkali-soluble resin (A-1) has a T SP The value may be 0.4 to 2.1, preferably 1.3 to 1.4. The T SP The value may be 1.2 to 2.1, preferably 1.8 to 2.1. SP The value may be 1.3 to 2.2, preferably 1.6 to 1.9.
[0027] In the context of this specification, T SP =(T PoB +T Soft ) / T PoB In the above formula, T PoB is the post-baking temperature during patterning, T Soft It is the softening point of the alkali-soluble resin (A) or the multifunctional epoxy oligomer (B).
[0028] The present invention can provide a curable resin composition as follows: for a pattern formed after photocuring, a thermal curing reaction is easily carried out due to an alkali-soluble resin and a multifunctional epoxy oligomer having a suitable softening point at the temperature of the thermal curing process, thereby being able to produce a pattern with improved chemical resistance. Specifically, the curable resin composition of the present invention is characterized in that it can be cured at 80°C to 230°C, and in particular, it can be cured at a low temperature of 80°C to 100°C. Therefore, when a pattern is formed on a substrate of a flexible polymer material, it has the advantage of being able to improve the chemical resistance of the pattern.
[0029] Preferably, when the curable resin composition of the present invention is used to make a pattern, the post-baking temperature (T PoB ) is 80°C to 100°C, the alkali-soluble resin (A) may include a SP The photocurable alkali-soluble resin (A-1) and T SP The value of T of the thermosetting alkali-soluble resin (A-2) is 1.8 to 2.1, and the T of the polyfunctional epoxy oligomer (B) is SP The value of may be 1.6 to 1.9. Such a curable resin composition of the present invention has a resin composition having a softening point suitable for the thermal curing temperature and satisfies the above range of T SP value, so the thermal curing reaction is easy to proceed and it is possible to produce a pattern with improved chemical resistance, adhesion to the underlying substrate and curing density, without surface damage or swelling or film shrinkage. It is particularly suitable for producing patterns for organic light-emitting display devices that require a low-temperature process temperature below 100°C.
[0030] Alkali soluble resin (A)
[0031] In the present invention, the alkali-soluble resin (A) is a component that imparts solubility to an alkali developer used in a development process when forming a pattern, and may include a photocurable alkali-soluble resin (A-1) and / or a thermosetting alkali-soluble resin (A-2). SP There is no special limit on the value of .
[0032] In one embodiment, the alkali-soluble resin (A) may contain carboxylic acid at the terminal group.
[0033] In the process of forming a pattern using the curable resin composition of the present invention, the post-baking temperature is referred to as T PoB The softening point of the alkali-soluble resin (A) is referred to as T Soft , and (T PoB +T Soft ) / T PoB The value of T SP When the alkali-soluble resin (A) is selected from T SP The photocurable alkali-soluble resin (A-1) and T SP The value of is 1.2 to 2.1, preferably 1.8 to 2.1, of one or more thermosetting alkali-soluble resins (A-2). Therefore, there can be an advantage that the curing reaction in the coating film is easily advanced in the thermosetting step.
[0034] The above-mentioned photocurable alkali-soluble resin (A-1) and / or the above-mentioned thermosetting alkali-soluble resin (A-2) are heated at the above-mentioned post-baking temperature (T PoB ) is 80℃~230℃, the above T SP The value of T is preferably satisfied when the post-baking temperature is 80°C to 100°C SP The value of T is preferably satisfied when the post-baking temperature is 80°C to 90°C. SP The value of .
[0035] More specifically, the post-baking temperature (T PoB ) is 80°C to 100°C, it is preferred to use T as the photocurable alkali-soluble resin (A-1). SP As the thermosetting alkali-soluble resin (A-2), a resin having a T value of 1.3 to 1.4 is preferably used. SP Resin with a value of 1.8 to 2.1.
[0036] As an example, the alkali-soluble resin (A) may include the photocurable alkali-soluble resin (A-1) and the thermosetting alkali-soluble resin (A-2) in a weight ratio of 1:0 to 0:1, preferably in a weight ratio of 1:0, 0:1 or 0.5:0.5. Specifically, it is preferred that the photocurable alkali-soluble resin (A-1) and the thermosetting alkali-soluble resin (A-2) are included in the same weight ratio, or only the photocurable alkali-soluble resin (A-1) or only the thermosetting alkali-soluble resin (A-2). When the photocurable alkali-soluble resin (A-1) and the thermosetting alkali-soluble resin (A-2) are included in the above weight ratio, there is an advantage of showing an excellent film reduction rate in the developing process and the thermosetting process.
[0037] As an example, the softening point of the alkali-soluble resin (A) measured by the ring and ball method may be 30°C to 90°C, and the weight average molecular weight may be 5,000 to 30,000. More specifically, the softening point of the photocurable alkali-soluble resin (A-1) may be 30°C to 32°C, and the softening point of the thermosetting alkali-soluble resin (A-2) may be 80°C to 88°C. When the softening point is within the above range, the advantage of excellent hardness after the thermal curing process may be obtained, and when the weight average molecular weight is within the above range, the advantage of excellent alkali solubility of the unexposed portion in the development process may be obtained.
[0038] The content of the alkali-soluble resin (A) may be 20 to 50% by weight, preferably 30 to 40% by weight, relative to the total weight of the solid content in the composition. When the content is within the above range, the solubility in the developer is sufficient and the developability is excellent, and the mechanical properties of the pattern can be improved.
[0039] The alkali-soluble resin (A) and the polyfunctional epoxy oligomer (B) described below may be contained in a weight ratio of 1:0.1 to 1:0.5. In this case, there is an advantage that the unexposed portion exhibits excellent alkali solubility.
[0040] The alkali-soluble resin (A) and the photopolymerizable unsaturated monomer (C) described below may be contained in a weight ratio of 1:0.5 to 1:2. In this case, there may be advantages that the exposed portion exhibits an excellent pattern shape and an excellent film reduction rate.
[0041] Multifunctional epoxy oligomer (B)
[0042] In the present invention, the multifunctional epoxy oligomer (B) is a component that promotes the polymerization reaction of the alkali-soluble resin (A) and induces the formation of crosslinks. As long as it contains epoxy groups and satisfies the following T SP There is no special limit on the value of .
[0043] In one embodiment, the multifunctional epoxy oligomer (B) may include an aromatic and / or alicyclic ring structure.
[0044] Since the epoxy group of the polyfunctional epoxy oligomer (B) undergoes ring-opening to promote the polymerization reaction of the alkali-soluble resin (A), the epoxy group is preferably contained in the repeating unit of the oligomer to maximize the reaction promotion effect.
[0045] The post-baking temperature in the process of forming a pattern from the curable resin composition of the present invention is referred to as T PoB The softening point of the multifunctional epoxy oligomer (B) is referred to as T Soft , and (T PoB +T Soft ) / T PoB The value of T SP When the T of the multifunctional epoxy oligomer (B) is SP The value of 1.3 to 2.2 can have the advantage of exhibiting excellent ring-opening and reaction in the thermal curing step.
[0046] The multifunctional epoxy oligomer (B) is heated at the post-baking temperature (T PoB ) is 80℃~230℃, the above T SP The value of T is preferably satisfied when the post-baking temperature is 80℃~100℃ SP The value of T is preferably satisfied when the post-baking temperature is 80°C to 90°C. SP The value of .
[0047] More specifically, the post-baking temperature (T PoB ) is 80°C to 100°C, it is preferred to use T as the multifunctional epoxy oligomer (B). SP Resin with a value of 1.6 to 1.9.
[0048] In addition, the T of the curable resin composition of the present invention as a whole sp Value(T sp T PoB The total (Total) can be calculated by multiplying the percentage of each component in the total of 100 of the alkali-soluble resin (A) and the multifunctional epoxy oligomer (B) by T as shown in the following mathematical formula 1: sp The calculation is performed by adding up the values (however, when out of the above range of the present invention, the value is multiplied by 0).
[0049] Specifically, when the above T PoB When the temperature is 80℃, according to the following mathematical formula 1, T sp T PoB Total value (T sp80 total) is preferably less than 1.45. PoB When the temperature is 100℃, T sp T PoB Total value (T sp 100 total) is preferably 1.36 or more. PoB When the temperature is 230℃, according to the following mathematical formula 1, T sp T PoB Total value (T sp 230 total) is preferably 1.16 or more. sp T PoB When the total value is within the above range, excellent adhesion and film shrinkage change rate are expressed.
[0050] [Mathematical formula 1]
[0051]
[0052] In the above mathematical formula 1,
[0053] Total content = [(A-1) content + (A-2) content + (B) content],
[0054] The T of the alkali-soluble resin (A) and / or the multifunctional epoxy oligomer (B) is sp If the value does not satisfy the above range of the present invention, T sp Substitute the value into 0, for example, at T sp In the case of a total value of 80, substitute T PoB T at 80°C sp Value, at T sp 230 total value, substitute T PoB T at 230℃ sp value.
[0055] In one embodiment, the multifunctional epoxy oligomer (B) may have a softening point of 65° C. to 90° C., preferably 65° C. to 72° C., as measured by a ring and ball method, and an epoxy equivalent (EEW) of 250 g / eq. or less. When the softening point is within the above range, the polymerization reaction may be easily carried out in the thermal curing process, and when the epoxy equivalent is within the above range, the cured density may be high.
[0056] The content of the multifunctional epoxy oligomer (B) may be 1 to 15 wt %, preferably 3 to 10 wt %, relative to the total weight of the solid components in the composition. When the content is within the above range, the chemical resistance of the pattern can be improved.
[0057] The alkali-soluble resin (A) and the polyfunctional epoxy oligomer (B) may be contained in a weight ratio of 1:0.1 to 1:0.5. In this case, there may be an advantage that the unexposed portion exhibits excellent alkali solubility.
[0058] Photopolymerizable unsaturated monomer (C)
[0059] In the present invention, the photopolymerizable unsaturated monomer (C) is a compound that can be polymerized by the action of the photopolymerization initiator (D) described below, and is a component for increasing the crosslinking density and enhancing the mechanical properties of the pattern. Any material used in the art can be used without particular limitation.
[0060] In one embodiment, the photopolymerizable unsaturated monomer (C) may include a monofunctional monomer, a bifunctional monomer, and other multifunctional monomers.
[0061] Specific examples of the monofunctional monomer include nonylphenyl carbitol acrylate, 2-hydroxy-3-phenoxypropyl acrylate, 2-ethylhexyl carbitol acrylate, 2-hydroxyethyl acrylate, and N-vinyl pyrrolidone.
[0062] Specific examples of the bifunctional monomer include 1,6-hexanediol di(meth)acrylate, ethylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, bis(acryloyloxyethyl) ether of bisphenol A, and 3-methylpentanediol di(meth)acrylate.
[0063] Specific examples of the other polyfunctional monomers include trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, and dipentaerythritol hexa(meth)acrylate.
[0064] The content of the photopolymerizable unsaturated monomer (C) may be 30 to 70% by weight, preferably 40 to 50% by weight, relative to the total weight of the solid content in the composition. When the content is within the above range, the durability of the pattern and the developability of the composition can be improved.
[0065] The alkali-soluble resin (A) and the photopolymerizable unsaturated monomer (C) may be contained in a weight ratio of 1:0.5 to 1:2. In this case, there may be advantages that the exposed portion exhibits an excellent pattern shape and an excellent film reduction rate.
[0066] Photopolymerization initiator (D)
[0067] In the present invention, the photopolymerization initiator (D) can be used without particular limitation as long as it can polymerize the photopolymerizable unsaturated monomer (C).
[0068] In one embodiment, the photopolymerization initiator (D) may include at least one compound selected from the group consisting of acetophenone compounds, benzophenone compounds, triazine compounds, biimidazole compounds, thioxanthone compounds, and oxime ester compounds.
[0069] The content of the photopolymerization initiator (D) may be 1 to 10% by weight, preferably 2 to 8% by weight, relative to the total weight of the solid content in the composition. When the content is within the above range, the strength and linearity of the pattern can be improved.
[0070] The photopolymerization initiator (D) may be used in combination with a photopolymerization initiation aid. It is preferred that a photopolymerization initiation aid is used in combination with the photopolymerization initiator (D) because a composition containing the photopolymerization initiator achieves higher sensitivity and productivity is improved when the composition is used to form an organic insulating film.
[0071] The above-mentioned photopolymerization initiator aid can be used to improve polymerization efficiency. One or more compounds selected from the group consisting of amine compounds, alkoxyanthracene compounds, thioxanthone compounds, carboxylic acids and sulfonic acid compounds can be used, and preferably selected from the group consisting of carboxylic acids and sulfonic acid compounds.
[0072] The photopolymerization initiator aid is preferably used in an amount of usually 10 mol or less, preferably 0.01 to 5 mol per 1 mol of the photopolymerization initiator. When the photopolymerization initiator aid is used within the above range, polymerization efficiency can be improved and productivity improvement effect can be expected.
[0073] Solvent (E)
[0074] In the present invention, the solvent (E) may be any organic solvent commonly used in the art without particular limitation. Examples of the solvent (E) include ethers, acetates, aromatic hydrocarbons, ketones, alcohols, and esters, and one or more thereof may be selected for use, but the invention is not limited thereto.
[0075] The content of the solvent (E) may be a remainder such that the total weight of the composition becomes 100% by weight. Specifically, in the present invention, the "remainder" means the remainder such that the total weight of the composition including the essential components of the present invention and the additional components thereof becomes 100% by weight, and the meaning of the "remainder" does not limit the composition of the present invention to not including the additional components.
[0076] In one embodiment, the content of the solvent (E) can be 60 to 90% by weight, preferably 70 to 85% by weight, relative to the total weight of the composition. When the content of the solvent (E) is within the above range, coating by a coating device such as a roll coater, a spin coater, a slit spin coater, a slit coater (sometimes also referred to as a die coater), an inkjet printer, etc., tends to improve coating properties, and is therefore preferred.
[0077] Thiol compounds having three or more functional groups (F)
[0078] The curable resin composition of the present invention may further contain a trifunctional or higher-functional thiol compound (F) in addition to the above-mentioned components as needed by a person skilled in the art within a range not impairing the object of the present invention.
[0079] The trifunctional or higher thiol compound (F) is a primary ring-opening agent that opens the epoxy group of the multifunctional epoxy oligomer (B). When used together with the alkali-soluble resin (A) and the multifunctional epoxy oligomer (B), the crosslinking density can be increased, the durability of the photocured pattern and the adhesion to the substrate can be improved, and yellowing at high temperatures can be prevented.
[0080] The trifunctional or higher-functional thiol compound (F) is not particularly limited as long as it can be used as a trifunctional or higher-functional thiol compound in the curable resin composition, and is preferably a tetrafunctional or higher-functional thiol compound. For example, the trifunctional or higher-functional thiol compound (F) may be 1,3,5-tris(3-mercaptobutyloxyethyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, trimethylolpropane tris(3-mercaptopropionate), pentaerythritol tetrakis(3-mercaptobutyrate), pentaerythritol tetrakis(3-mercaptopropionate), dipentaerythritol hexa(3-mercaptopropionate), tetraethylene glycol bis(3-mercaptopropionate), etc., but is not limited thereto.
[0081] The content of the trifunctional or higher thiol compound (F) may be 1 to 20% by weight, preferably 2 to 10% by weight, relative to the total weight of the solid content in the composition. When the content is within the above range, excellent curing performance can be exhibited at low temperatures.
[0082] Additives (G)
[0083] The curable resin composition of the present invention may further contain an additive (G) in addition to the above-mentioned components as needed by those skilled in the art within a range not impairing the object of the present invention.
[0084] The additive (F) may include at least one selected from the group consisting of, for example, antioxidants, surfactants, etc., but is not limited thereto.
[0085] The additive (F) can be appropriately added by a person skilled in the art within the scope of not impairing the effect of the present invention. For example, the additive (F) can be used in an amount of 0.05 to 10 parts by weight, preferably 0.1 to 10 parts by weight, and more preferably 0.1 to 5 parts by weight, relative to 100 parts by weight of the curable resin composition as a whole, but is not limited thereto.
[0086] <Pattern>
[0087] The pattern of the present invention can be produced by a method known in the art other than being formed from the above-mentioned curable resin composition.
[0088] As an example, the pattern may be a pattern selected from the group consisting of an array planarization film pattern, a protection film pattern, an insulation film pattern, a photoresist pattern, a black matrix pattern, a column spacer pattern, and a black column spacer pattern.
[0089] <Image Display Device>
[0090] In addition to the above-mentioned pattern, the image display device of the present invention includes a structure known in the technical field. As specific examples, there can be cited liquid crystal display devices, organic light emitting diodes (OLEDs), flexible displays, electroluminescent display devices, plasma display devices, field emission display devices, etc. It is most preferably used in organic light emitting display devices, but is not limited to this.
[0091] Hereinafter, the present invention will be described in more detail using examples and comparative examples. However, the following examples are for illustrating the present invention, and the present invention is not limited to these examples, and various modifications and changes can be made.
[0092] Synthesis Example 1: Synthesis of photocurable alkali-soluble resin (A-1-1)
[0093] In a flask equipped with a stirrer, a thermometer, a reflux condenser, a dropping funnel, and a nitrogen inlet tube, 100 parts of propylene glycol monomethyl ether acetate, 100 parts of propylene glycol monomethyl ether, 5 parts of AIBN, 23.0 parts of vinyl toluene, 1.6 parts of 4-methylstyrene, 46.0 parts of glycidyl methacrylate, and 3 parts of n-dodecyl mercaptan were added and replaced with nitrogen. After stirring, the temperature of the reaction liquid was raised to 80°C and reacted for 4 hours. Next, the temperature of the reaction liquid was lowered to room temperature, and after the atmosphere in the flask was replaced from nitrogen to air, 0.2 parts of triethylamine, 0.1 parts of 4-methoxyphenol, and 23.3 parts of acrylic acid were added, and the reaction was carried out at 100°C for 6 hours. After that, the temperature of the reaction liquid was lowered to room temperature, 6.0 parts of succinic anhydride were added, and the reaction was carried out at 80°C for 6 hours.
[0094] The alkali-soluble resin synthesized in this way had a solid content acid value of 32.8 mgKOH / g, a weight average molecular weight Mw measured by GPC of about 6,350, a repeating unit represented by the following chemical formula 1 of 70 mol %, and a softening point measured by a ring and ball method of 30°C.
[0095] [Chemical formula 1]
[0096]
[0097] Synthesis Example 2: Synthesis of photocurable alkali-soluble resin (A-1-2)
[0098] In a flask equipped with a stirrer, a thermometer, a reflux condenser, a dropping funnel, and a nitrogen inlet tube, 120 parts of propylene glycol monomethyl ether acetate, 80 parts of propylene glycol monomethyl ether, 2 parts of AIBN, 13.0 parts of the above acrylic acid, 10 parts of benzyl methacrylate, 57.0 parts of 4-methylstyrene, 20 parts of methyl methacrylate, and 3 parts of n-dodecyl mercaptan were added and replaced with nitrogen. Thereafter, the temperature of the reaction solution was raised to 80° C. with stirring and reacted for 8 hours.
[0099] The solid content acid value of the alkali-soluble resin synthesized in this way was 98.2 mgKOH / g, and the weight average molecular weight Mw measured by GPC was about 14,950. The softening point measured by the ring and ball method was 95°C.
[0100] Synthesis Example 3: Synthesis of thermosetting alkali-soluble resin (A-2-1)
[0101] In a 1L flask equipped with a reflux condenser, a dropping funnel and a stirrer, nitrogen gas was flowed at 0.02L / min to form a nitrogen atmosphere, and 150g of diethylene glycol methyl ethyl ether was added and heated to 70°C while stirring. Next, 132.2g (0.60mol) of the compound represented by the above chemical formula 1, 55.3g (0.30mol) of 3-ethyl-3-oxetane methacrylate and 8.6g (0.10mol) of methacrylic acid were dissolved in 150g of diethylene glycol methyl ethyl ether to prepare a solution. The prepared solution was dripped into the flask using a dropping funnel, and then a solution prepared by dissolving 27.9g (0.11mol) of a polymerization initiator 2,2'-azobis(2,4-dimethylvaleronitrile) in 200g of diethylene glycol methyl ethyl ether was dripped into the flask using another dropping funnel over 4 hours.
[0102] After the addition of the polymerization initiator solution was completed, the temperature was maintained at 70°C for 4 hours and then cooled to room temperature. The solid content of the alkali-soluble resin synthesized in this way was 41.8% by mass, the solid content-converted acid value was 62 mgKOH / g, and the weight average molecular weight Mw measured by GPC was about 7,700. The softening point measured by the ring and ball method was 87°C.
[0103] Synthesis Example 4: Synthesis of thermosetting alkali-soluble resin (A-2-2)
[0104] After the solution of the polymerization initiator was completely added dropwise, it was maintained at 70 °C for 8 hours, and otherwise, it was carried out in the same manner as in Synthesis Example 3 above.
[0105] The solid content of the alkali-soluble resin thus synthesized was 41.8% by mass, the acid value in terms of solid content was 42 mg KOH / g, the weight-average molecular weight Mw measured by GPC was about 12,300, and the softening point measured by the ring and ball method was 103 °C.
[0106] Preparation of curable resin compositions of Examples and Comparative Examples
[0107] Refer to Table 1 below to prepare the curable resin compositions of the production examples and comparative examples.
[0108] [Table 1]
[0109]
[0110] <A: Alkali-soluble resin>
[0111] -A-1-1: Photo-curable alkali-soluble resin of Synthesis Example 1 (softening point 30 °C)
[0112] -A-1-2: Photo-curable alkali-soluble resin of Synthesis Example 2 (softening point 95 °C)
[0113] -A-2-1: Thermo-curable alkali-soluble resin of Synthesis Example 3 (softening point 87 °C)
[0114] -A-2-2: Thermo-curable alkali-soluble resin of Synthesis Example 4 (softening point 103 °C)
[0115] <B: Polyfunctional epoxy oligomer>
[0116] -B-1: EXA-7241 (manufactured by DIC, softening point 66 °C, epoxy equivalent 168 g / eq.)
[0117] -B-2: KBPN-110 (manufactured by Kukdo Chemical, softening point 65 °C, epoxy equivalent 210 g / eq.)
[0118] -B-3: HP-7200HHH (manufactured by DIC, softening point 102 °C, epoxy equivalent 286 g / eq.)
[0119] -B-4: HP-9900-75M (manufactured by DIC, softening point 101 °C, epoxy equivalent 274 g / eq.)
[0120] <C: Photopolymerizable unsaturated monomer>
[0121] - Dipentaerythritol hexaacrylate (KAYARAD DPHA: manufactured by Nippon Kayaku Co., Ltd.)
[0122] <D: Photoinitiator>
[0123] - Irgacure OXE - 01 (manufactured by BASF Corporation)
[0124] <E: Solvent>
[0125] - Propylene glycol monomethyl ether acetate
[0126] <F: Thiol compound with 3 or more functional groups>
[0127] - Trimethylolpropane tris(3 - mercaptopropionate) (manufactured by SC Organic Chemistry Co., Ltd.)
[0128] <G: Additive>
[0129] - Sumilizer GP (manufactured by Sumitomo Chemical)
[0130] Experimental Example 1. Physical Property Evaluation 1 of Pattern
[0131] A 5×5 cm glass substrate (Eagle 2000; manufactured by Corning Inc.) was successively cleaned with neutral detergent, water, and ethanol and then dried. The curable resin compositions prepared in the above Examples and Comparative Examples were spin - coated on this glass substrate, and then pre - baked on a hot plate at 80°C for 120 seconds. After cooling the pre - baked substrate to room temperature, the distance from the quartz glass photomask was set to 50 μm, and light was irradiated using an exposure machine (MA6; manufactured by Karl suss Co., Ltd.) at an exposure dose of 30 mJ / cm 2 (based on 365 nm) of light. At this time, a photomask having a square opening (hole pattern) of 30 μm squares and spaced 100 μm apart from each other on the same plane was used as the photomask. After light irradiation, it was developed in a 2.38 wt% aqueous solution of tetramethylammonium hydroxide for 60 seconds, washed with ultrapure water, and dried under nitrogen, thereby forming a pattern on the curable resin composition film. Post - baking was carried out in an oven at 80°C for 2 hours. For the pattern thus obtained, the following physical property evaluations (1) and (2) were carried out, and the results are shown in Table 2 below.
[0132] Experimental Example 2. Physical Property Evaluation 2 of Pattern
[0133] Post - baking was carried out at 100°C for 1 hour, and otherwise, the same procedure as in Experimental Example 1 was carried out. For the pattern thus obtained, the following physical property evaluations (1) and (2) were carried out, and the results are shown in Table 2 below.
[0134] Experimental Example 3. Physical Property Evaluation of Pattern 3
[0135] The same procedure as in Experimental Example 1 was carried out except that post-baking was performed at 230° C. for 30 minutes. The patterns obtained in this manner were subjected to the following physical property evaluations (1) and (2). The results are shown in Table 2 below.
[0136] (1) Adhesion evaluation
[0137] The patterns prepared in Experimental Examples 1 to 3 were immersed in an NMP aqueous solution for 6 minutes and then taken out. Thereafter, the adhesiveness was evaluated by attaching and removing a tape on a surface cut by a knife according to the ASTM D-3359-08 standard test conditions.
[0138] The degree of film peeling in the cutting / tape test after the reagent treatment was classified into 0B to 5B according to the standard test method, and 5B was judged to have the best performance.
[0139] <Evaluation Criteria>
[0140] 5B: Peel 0%
[0141] 4B: Peeling greater than 0% and less than 5%
[0142] 3B: Peeling is 5% or more and less than 15%
[0143] 2B: Peeling is 15% or more and less than 35%
[0144] 1B: Peeling is 35% or more and less than 65%
[0145] 0B: Peeling is more than 65%
[0146] (2) Film shrinkage evaluation
[0147] The thickness change of the patterns produced in Experimental Examples 1 to 3 was evaluated before and after the patterns were immersed in the NMP aqueous solution for 6 minutes.
[0148] <Evaluation Criteria>
[0149] ◎: Film thickness change is less than 1%
[0150] ○: Film thickness change is 1% or more and less than 2%
[0151] △: Film thickness change is 2% or more and less than 5%
[0152] X: Film thickness change is 5% or more
[0153] [Table 2]
[0154]
[0155] In addition, the following Table 3 shows the T values of the curable resin compositions of the examples and comparative examples in Experimental Examples 1 to 3. SP value.
[0156] Referring to Table 3 below, it can be confirmed that the T SP Value in T PoB At 80℃ and 230℃, it satisfies 0.4~2.1, but for A-1-2, at T PoB The above range was not satisfied at 80°C. SP Value in T PoB 1.2 to 2.1 are satisfied at 80℃ and 230℃, but for A-2-2, at T PoB The above range was not satisfied at 80°C. The T values of the multifunctional epoxy oligomers B-1 and B-2 were SP The value satisfies 1.3~2.2, but for B-3 and B-4, the PoB At 80°C, the above range is not met.
[0157] [Table 3]
[0158]
[0159] In addition, in the following Table 4, for Examples 1 to 11 and Comparative Examples 1 to 7 in which the weight ratio of the alkali-soluble resin (A) to the multifunctional epoxy oligomer (B) is in the range of 1:0.1 to 1:0.5 and the weight ratio of the alkali-soluble resin (A) to the photopolymerizable unsaturated monomer (C) is in the range of 1:0.5 to 1:2, the T in Experimental Example 1 was calculated. sp T PoB Total(T sp 80 total).
[0160] About T sp T PoB Total value, at T PoB T at 80℃~230℃ sp When the above range is met, the T sp The value is multiplied by the percentage of each component relative to the total of the alkali-soluble resin (A) and the multifunctional epoxy oligomer (B), and the result is calculated using the T PoB T at 80℃~230℃ sp In the case of substances outside the above range (A-1-2, A-2-2, B-3 and B-4), the values are multiplied by 0, and the film shrinkage change and adhesion are shown in relation to T sp T PoB Total correlation.
[0161] Table 4 below shows the T values of the patterns produced at a post-baking temperature of 80°C. sp T PoB The total value will be for T sp The results of the 80 total are shown in Figure 1 and Figure 2 In the sp T PoB The correlation between the total value of film shrinkage change and adhesion.
[0162] [Table 4]
[0163]
[0164] From the above table, it can be confirmed that for T sp As for the total value of 80, when it is 1.45 or more, the adhesion and the film shrinkage change rate tend to be excellent.
[0165] In addition, in the following Tables 5 and 6, the post-baking temperature in Table 4 was changed to 100°C or 230°C and the T sp T PoB In addition, the results of the summation of Tsp100 are shown in Figure 3 and Figure 4 In the sp The total results of 230 are shown in Figure 5 and Figure 6 In order to confirm the film shrinkage change and adhesion with T sp T PoB Total correlation. About T sp 100 Total value and T sp 230 Total value, used in T PoB 80℃~230℃T sp In the case of substances outside the above range (A-1-2, A-2-2, B-3 and B-4), the value was similarly multiplied by 0.
[0166] [Table 5]
[0167]
[0168] [Table 6]
[0169]
[0170] From the above table, it can be confirmed that for T sp As for the total value of 100, the adhesion and film shrinkage change rate tend to be excellent from 1.36 or more. sp As for the total value of 230, when it is 1.16 or more, the adhesion and the film shrinkage change rate tend to be excellent.
Claims
1. A curable resin composition, characterized in that The composition comprises an alkali-soluble resin (A), a multifunctional epoxy oligomer (B), a photopolymerizable unsaturated monomer (C), a photopolymerization initiator (D), a trifunctional or higher thiol compound (F) and a solvent (E), The alkali-soluble resin (A) comprises a photocurable alkali-soluble resin (A-1) and a thermosetting alkali-soluble resin (A-2), The photocurable alkali-soluble resin (A-1) comprises vinyltoluene, 4-methylstyrene and glycidyl methacrylate, The alkali-soluble resin (A) has a softening point of 30° C. or more and 90° C. or less as measured by a ring and ball method. The multifunctional epoxy oligomer (B) has a softening point of 65° C. to 90° C. as measured by a ring and ball method, The photocurable alkali-soluble resin (A-1) has a softening point of 30° C. to 32° C., The softening point of the thermosetting alkali-soluble resin (A-2) is 80° C. or higher and 88° C. or lower. When the post-baking temperature is within the range of 80℃~230℃, PoB , and the softening point of the alkali-soluble resin (A) or the multifunctional epoxy oligomer (B) is T Soft When (T PoB +T Soft ) / T PoB The value of T SP , The alkali-soluble resin (A) comprises a SP The photocurable alkali-soluble resin (A-1) and T SP One or more thermosetting alkali-soluble resins (A-2) having a value of 1.2 to 2.1, The epoxy equivalent weight (EEW) of the multifunctional epoxy oligomer (B) is 250 g / eq. or less and T SP The value is 1.3~2.
2. 2 . The curable resin composition according to claim 1 , wherein a weight ratio of the alkali-soluble resin (A) to the multifunctional epoxy oligomer (B) is 1:0.1 to 1:0.
5. 3 . The curable resin composition according to claim 1 , wherein the alkali-soluble resin (A) has a weight average molecular weight of 5,000 to 30,000. 4 . The curable resin composition according to claim 1 , wherein a weight ratio of the alkali-soluble resin (A) to the photopolymerizable unsaturated monomer (C) is 1:0.5 to 1:
2.
5. The curable resin composition according to claim 1, characterized in that The curable resin composition can be cured at 80°C to 230°C. 6 . A pattern formed from the curable resin composition according to claim 1 .
7. The pattern according to claim 6, characterized in that The pattern is selected from the group consisting of an array planarization film pattern, a protection film pattern, an insulation film pattern, a photoresist pattern, a black matrix pattern, a column spacer pattern, and a black column spacer pattern.
8. An image display device comprising the pattern according to claim 6.